Hubungan Asupan Gizi, Aktivitas Fisik, dan Status Gizi dengan Tekanan Darah Lansia di Bekasi, Jawa Barat: Association of Nutrient Intake, Physical Activity, Nutritional Status, and Blood Pressure Among Elderly in Bekasi, West Java - Hayati, Salmah Hayati; Dainy, Nunung Cipta; Hayati, Salmah (Jurnal Ilmu Gizi dan Dietetik, 2026)
Older adults are a population group that continues to increase each year and is vulnerable to various health problems, including hypertension. The prevalence of hypertension in Indonesia remains high. Based on the 2018 Basic Health Research (Riskesdas), the prevalence reached 57.6%. In West Java, the prevalence was 71.08%, while in Bekasi City it increased from 29.2% in 2013 to 39.6% in 2018. One of the government’s efforts to control non-communicable diseases (NCDs) is through community-based health services such as integrated health service posts (Posyandu) and integrated non-communicable disease posts (Posbindu) for older adults. This study aimed to analyze the relationship between nutritional status, nutrient intake (sodium and fat), and physical activity with blood pressure among older adults at Posbindu Anyelir, North Bekasi District. This study used a descriptive correlational design with a cross-sectional approach. A total of 70 older adults who met the inclusion and exclusion criteria participated in the study. Data were collected through questionnaires and direct measurements and analyzed using the chi-square test. The results showed that the prevalence of hypertension was 37.1%. There was no significant relationship between nutritional status (p=0.194) and physical activity (p=0.749) with blood pressure. However, sodium intake (p<0.001) and fat intake (p=0.049) were significantly associated with blood pressure. These findings highlight the importance of nutrition education to control sodium and fat intake as part of hypertension prevention among older adults.